Copper oxide nanoplatelets and nanoflowers: facile synthesis and catalytic activity in oxidative degradation of methylene blue. (1st July 2014) - Liao, Jinyun; Li, Hao; Zhang, Xibin; Xiao, Dinshu
Abstract : CuO nanostructures with controlled morphology have received a great deal of attention on account of their interesting physicochemical properties and wide applications in different areas. In this reported study, CuO nanoplatelets and CuO nanoflowers assembled by nanoplatelets were synthesised by a facile hydrothermal approach. It was found that the as‐prepared CuO samples exhibited higher catalytic activity than the recently reported CuO nanostructures in the oxidative degradation of methylene blue with hydrogen peroxide. In addition, it was revealed that CuO nanoflowers display higher intrinsic catalytic activity than CuO nanoplatelets, which may result from their special three‐dimensional nanostructures.